(untitled) (Experimental biology, 2022)
One of the earliest biotechnological applications of enzymes is cheese production. The high specific milk-clotting activity of chymosin gives it an advantage over other proteases in the cheese industry. The action of chymosin is based on hydrolysis of the bond between the amino acid residues Phe105 and Met106 in the κ-casein molecule, which causes destabilisation of casein micelles, coagulation of milk and its separation into a clot and a whey. A recombinant chymosin of the camel Camelus Bactrianus was obtained using the yeast producer strain Pichia pastoris GS115/pGAPZαA/ProchymCB. The recombinant chymosin was purified by ion exchange chromatography. The milk-clotting activity of recombinant camelian chymosin against mare’s milk was studied as a function of pH and temperature. It was found that the optimum value at which the maximum activity of recombinant camel’s chymosin with respect to mare’s milk is observed is pH 4.0 and the optimum temperature is 70°C. The activity of recombinant camel chymosin on mare, cow and goat milk was 123, 9605 and 4650 units/mg, respectively. Recombinant camel chymosin was shown to have high coagulation activity, sufficient to produce curd and cheese. The yield of cheese clot from 6 l of goat milk was 936 grams. Recombinant camel chymosin has prospects for use in cow’s and goat’s milk processing and cheese production technologies.